2020
DOI: 10.3390/ijms21207799
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Methods for Studying Structure and Interactions of Macrolide Antibiotics

Abstract: Macrolide antibiotics are macrocyclic compounds that are clinically used and prescribed for the treatment of upper and lower respiratory tract infections. They inhibit the synthesis of bacterial proteins by reversible binding to the 23S rRNA at or near the peptidyl transferase center. However, their excellent antibacterial profile was largely compromised by the emergence of bacterial resistance. Today, fighting resistance to antibiotics is one of the greatest challenges in medicinal chemistry. Considering vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 118 publications
(178 reference statements)
0
9
0
3
Order By: Relevance
“…The aminopropyl–azithromycin derivatives 1a – c are precursors in the synthesis of macrozones, the novel bioactive azithromycin–thiosemicarbazone conjugates [ 1 , 2 ]. The compounds 1a – c have shown promising activity against some Gram-positive and Gram- negative bacteria, including efflux-resistant S. pneumoniae and S. pyogenes strains and a Gram-negative E. coli strain against which azithromycin is inactive ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aminopropyl–azithromycin derivatives 1a – c are precursors in the synthesis of macrozones, the novel bioactive azithromycin–thiosemicarbazone conjugates [ 1 , 2 ]. The compounds 1a – c have shown promising activity against some Gram-positive and Gram- negative bacteria, including efflux-resistant S. pneumoniae and S. pyogenes strains and a Gram-negative E. coli strain against which azithromycin is inactive ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Macrozones belong to a novel class of azithromycin–thiosemicarbazone conjugates that exhibit very good antibacterial activities against both susceptible and some resistant bacterial strains, such as efflux- and MLS (macrolides–lincosamides–streptogramines)- resistant S. aureus , S. pneumoniae and S. pyogenes strains [ 1 , 2 ]. Macrolide antibiotics, such as azithromycin, have been in clinical use for over 50 years, mostly due to their high efficacy, safety and favorable pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Review [ 158 ] presents information that is very rarely found in the modern chemical literature, namely, about azulene derivatives with heterocyclic fragments in the molecule, the specifics of their synthesis, and the prospects for their application in materials science. In review [ 161 ], devoted to the so-called macrolide antibiotics, a description of advanced physicochemical methods for elucidating the structure and interaction of macrolide antibiotics in solid state and solution is presented, and their main advantages and disadvantages are considered. Finally, review [ 176 ] systematizes and characterizes the latest advances in precision rotational-vibrational spectroscopy of neutral (mainly organic) molecules, within which spectra are obtained by using infrared frequency combs, either as direct probe sources or as ultra-accurate optical rulers.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…Such a scenario could soon be true for the field of RNA structure modeling, thus resulting in a fast and marked increase in the volume of available RNA tertiary structures. Advancements in cryogenic electron microscopy (cryo-EM) technology have enabled large RNA-protein or RNA-only complexes to be solved, thus initiating an RNA structure renaissance; this has ignited interest on whether many RNA structures, other than those already known as drug targets, may also contain binding pockets that could be targeted for therapeutic applications [39,40]. The more complex structures also made clear that the arrangements of base-base interactions were much more diverse than the canonical interactions observed for DNA [41].…”
Section: Introductionmentioning
confidence: 99%